Combined delivery of IL12 and an IL18 mutant without IL18BP-binding activity by an adenoviral vector enhances tumor specific immunity - Yan Cheng; Renjie Luo; Erguang Li (Scientific Reports)
Abstract Cytokines play pivotal roles in anticancer immune response. We previously reported that adenovirus armed with an IL18 variant (DR18) that overcomes IL18BP neutralizing effect displayed powerful therapeutic effects in local and distant tumors when delivered intratumorally. Here, we tested a combined delivery of IL12 and DR18 in tumor models since IL12 and IL18 are known to act synergistically in potentiating IFNγ production and antitumor immunity. To minimize adverse effects associated with systemic delivery, we constructed oncolytic adenoviruses (oAd) harboring DR18 and IL12 (oAd.DR18/IL12). IL12 was expressed as a single chain IL12 (scIL12) peptide composed of the IL12/p40 and IL12/p35 subunits. Intratumoral administration of oAd.DR18/IL12, oAd-expressing DR18 (oAd.DR18), or oAd-expressing IL12 (oAd.IL12) showed antitumor effect in syngeneic colorectal tumor models. Compared to oAd.DR18 or oAd.IL12, administration of oAd.DR18/IL12 improved the antitumor effects as well as increased survival rate in these models. We detected enhanced tumor infiltrating T lymphocytes and NK cells in oAd.DR18/IL12-treated mice than those from mock-treated or individually treated groups. Moreover, mice received oAd.DR18/IL12 had more robust tumor-specific cytotoxicity. Importantly, mice that had tumor regression after oAd.DR18/IL12 treatment established anti-tumor specific immune memory. These results show that adenovirus armed with engineered cytokines boosts tumor specific immunity and antitumor effect.